Wavelength routed optical neural networks - Dymich, Stepan; Kaidan, Mykola; Strykhaluik, Bogdan; Yaremko, Oleg; Melnyk, Oksana (Видавництво Львівської політехніки, 2012)
In this paper wavelength routed optical neural networks are presented. Characteristics of low-oriented models of routing were classified.
Keywords: Optical neural networks; wavelength routed; routing